2016
DOI: 10.1104/pp.16.00435
|View full text |Cite
|
Sign up to set email alerts
|

eIF4A RNA Helicase Associates with Cyclin-Dependent Protein Kinase A in Proliferating Cells and Is Modulated by Phosphorylation

Abstract: Eukaryotic initiation factor 4A (eIF4A) is a highly conserved RNA-stimulated ATPase and helicase involved in the initiation of messenger RNA translation. Previously, we found that eIF4A interacts with cyclin-dependent kinase A (CDKA), the plant ortholog of mammalian CDK1. Here, we show that this interaction occurs only in proliferating cells where the two proteins coassociate with 59-cap-binding protein complexes, eIF4F or the plant-specific eIFiso4F. CDKA phosphorylates eIF4A on a conserved threonine residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 70 publications
(104 reference statements)
2
30
0
Order By: Relevance
“…The helicase eIF4A is also known to be phosphorylated in response to heat and hypoxia (Webster et al ., ; Le et al ., ). It has recently been found that the phosphorylation of eIF4A in proliferating cells is mediated by CYCLIN‐DEPENDENT PROTEIN KINASE A (CDKA), and the results from this research suggest that this phosphorylation downregulates the activity of eIF4A, and therefore affects translation negatively (Bush et al ., ).…”
Section: Global Changes In Translationmentioning
confidence: 97%
“…The helicase eIF4A is also known to be phosphorylated in response to heat and hypoxia (Webster et al ., ; Le et al ., ). It has recently been found that the phosphorylation of eIF4A in proliferating cells is mediated by CYCLIN‐DEPENDENT PROTEIN KINASE A (CDKA), and the results from this research suggest that this phosphorylation downregulates the activity of eIF4A, and therefore affects translation negatively (Bush et al ., ).…”
Section: Global Changes In Translationmentioning
confidence: 97%
“…This interaction is also a rate limiting step ensuring differential translation (Bush et al, 2015). In the Arabidopsis genome, two genes encode eIF4A, EIF4A1 and EIF4A2 , but only EIF4A1 knock-out mutants exhibit altered growth and cell size in a cell type-specific manner (Bush et al, 2015; Bush et al, 2016). These growth and cell size defects are partly similar to TaMAB2 -overexpression effects supporting the conclusion that eIF4A, which is highly conserved in eukaryotes (Bush et al, 2015), is potentially a TaMAB2 substrate.…”
Section: Discussionmentioning
confidence: 99%
“…TOR kinase additionally signals to a variety of translation-relevant proteins including MRFs, which are partners of eIF4A helicase, the RP eS6, and the inhibitor of Pol III, MAF1 (Ahn et al, 2019;Bush et al, 2016;D. H. Lee et al, 2017).…”
Section: Tor Kinase Signalingmentioning
confidence: 99%